Do Oil Industry Merger Waves Reveal Any Trends? - Barrows, Samuel D. (International Journal of Energy Economics and Policy, 2017)
The dynamics of the stock prices of oil industry acquirer companies are studied during in-wave and out-wave years between 1998 and 2013. The research question is do oil industry merger waves reveal any trends? This quantitative study focuses on stock returns of acquirer companies over a four-year horizon for each merger transaction. Portfolios created from these transactions provide a comparison between in-wave and out-wave years. Three benchmarks are incorporated to provide various economic adjustment factors. Six cases are presented whose outcome largely follow other similar studies. The main contribution of the study is the identification of a dynamic during oil industry in-wave years which sees a substantial increase in the Brent oil market price, of at least 29% for these in-wave years. This dynamic is not identified previously in the literature. Keywords: Oil Industry Mergers, Waves, Crude Oil Price, 1998-2013 JEL Classifications: G15, G34, P18